Competition between supernucleation and plasticization in the crystallization and rheological behavior of PCL/CNT‐based nanocomposites and nanohybrids. Issue 17 (14th June 2017) - Vega, Juan F.; Fernández‐Alcázar, Joel; López, Juan V.; Michell, Rose Mary; Pérez‐Camargo, Ricardo A.; Ruelle, Benoit; Martínez‐Salazar, Javier; Arnal, María Luisa; Dubois, Philippe; Müller, Alejandro J.
ABSTRACT: PCL was blended with pristine multiwalled carbon nanotubes (MWCNT) and with a nanohybrid obtained from the same MWCNT but grafted with low molecular weight PCL, employing concentrations of 0.25 to 5 wt % of MWCNT and MWCNT‐ g ‐PCL. Excellent CNT dispersion was found in all samples leading to supernucleation of both nanofiller types. Nanohybrids with 1 wt % or less MWCNTs crystallize faster than nanocomposites (due to supernucleation), while the trend eventually reverses at higher nanotubes content (because of plasticization). Rheological results show that yield‐like behavior develops in both nanocomposites, even for the minimum content of carbon nanotubes. In addition, the MWCNT‐ g ‐PCL family, when compared with the neat polymer, exhibits lower values of viscosity and modulus in oscillatory shear, and higher compliance in creep. These rheological differences are discussed in terms of the plasticization effect caused by the existence of low molecular weight free and grafted PCL chains in the nanohybrids. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1310–1325 Abstract : Pristine multiwalled carbon nanotubes (MWCNT) and MWCNT grafted to poly(ε‐caprolactone) (MWCNT‐ g ‐PCL) were blended with neat PCL. Excellent MWCNTs dispersion and supernucleation effects of both kinds of nanofillers were found. The low molecular weight free and grafted PCL chains present in PCL/MWNCNT‐ g ‐PCL blends provoked plasticization effects that compete with supernucleation.